اقبال کے رنگِ نعت سے اکیسویں صدی کے نعت نگاروں کی اثرپذیری: ایک تحقیقی مطالعہ: The Influence of Iqbal’s Rang-e-Naat on 21st Century Naat Writers: A Research Study - Iqbali, Dr. Hassan Raza (Zoraiz, 2025)
Allama Muhammad Iqbal (1877-1938) revolutionized Urdu Naat by infusing it with intellectual and artistic depth, transcending traditional devotional expressions. Inspired by the Holy Prophet’s (PBUH) life, Iqbal’s Naat integrates metaphysical and universal themes with national and cultural narratives, employing modern poetic forms like rubai, masnavi, and musaddas. His approach, marked by thematic diversity and stylistic innovation, set a new paradigm for Naat. This influence is evident in 21st-century poets like Hafeez Taib, Muzaffar Warsi, Sabih Rehmani, and others, who adopt Iqbal’s style to reflect contemporary issues such as moral decline, political instability, and global Muslim struggles. By aligning Naat with modern sensibilities, these poets enrich it with symbolic and metaphorical expressions, resonating with Iqbal’s vision of universal spirituality and reform. This study examines Iqbal’s intellectual and stylistic contributions, analyzing how his legacy shapes the thematic and aesthetic evolution of 21st-century Urdu Naat, making it a powerful medium for spiritual reflection and socio-political commentary.